2014
DOI: 10.3126/ijasbt.v2i3.11001
|View full text |Cite
|
Sign up to set email alerts
|

Tillage, Residue, Fertilizer and Weed Management on Phenology and Yield of Spring Maize in Terai, Nepal

Abstract: With the aim of developing crop management technologies that reduce the yield gap of maize (Zea mays L.) in Nepal, a study was carried-out to determine whether the grain yield of maize could be manipulated through tillage, residue, and nutrient and weed management practices. The effect of tillage (conventional and no tillage), residue (residue retained and residue removed), fertilizer (recommended doses of fertilizer and farmers' doses of fertilizer) and weed management practices (herbicide use and manual weed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Grain yield of maize was significantly higher in EI practice as it comprised all recommended agronomic practices which included conservation tillage, crop residue cover, optimum planting density, precision nutrient management, application of water at critical growth stages, integrated weed, disease, and insect compared to FP and other treatments which were deficit in one or another best crop management practices. Grain yield was significantly higher in residue cover in comparison with conventional tillage and residue removed 27 . But in the case of EI-IWM, grain yield was not significantly influenced by residue cover (Table 1 ).…”
Section: Discussionmentioning
confidence: 88%
“…Grain yield of maize was significantly higher in EI practice as it comprised all recommended agronomic practices which included conservation tillage, crop residue cover, optimum planting density, precision nutrient management, application of water at critical growth stages, integrated weed, disease, and insect compared to FP and other treatments which were deficit in one or another best crop management practices. Grain yield was significantly higher in residue cover in comparison with conventional tillage and residue removed 27 . But in the case of EI-IWM, grain yield was not significantly influenced by residue cover (Table 1 ).…”
Section: Discussionmentioning
confidence: 88%
“…It could also been resulted because of effect of compost in holding soil moisture. Dahal et al, (2014) reported that residue treated soil delayed in maturity of maize with the same justification given above and the significant increased soil water holding capacity and Vengadaramana and Jashothan (2012) reported that compost and cattle manure increased water retention in soil.…”
Section: Introductionmentioning
confidence: 75%
“…This study established that the Sentinel-2 based dataset is useful for automatically tracking crop dynamics in small-scale farms with heterogeneous topography. Before this study, phenology estimation had been realized based on a field survey [33,34] or coarse resolution remote sensing data such as MODIS time-series data [24,35,36]. However, field observation is time and resource consuming; hence, it cannot be extended to a larger area.…”
Section: Discussionmentioning
confidence: 99%